THE NUMBER AND SITUATION OF DISADVANTAGED CHILDREN IN SLOVAKIA AND THE FACTORS INFLUENCING THEIR PARTICIPATION IN SPORTS ACTIVITIES - Zidek, Péter; Müller, Anetta (Stadium - Hungarian Journal of Sport Sciences, 2024)
This research paper analyzes socially disadvantaged children in Slovakia, focusing on current statistics and factors influencing their engagement in sporting activities. Drawing on recent data, the study highlights the prevalence and distribution of socially disadvantaged groups among children in Slovakia. It also investigates the multifaceted factors impacting their participation in sports, including the roles of parents, peer groups, coaches, and other socio-cultural influences. By examining these factors, the research aims to understand the barriers and facilitators to sports participation among socially disadvantaged children. The findings contribute to the broader understanding of the intersection between socio-economic status and sports engagement, offering insights for policymakers, educators, and practitioners seeking to develop targeted interventions and programs to promote sports inclusion and equity among disadvantaged youth in Slovakia.